Pengaruh Jobsheet Terhadap Hasil Belajar Keterampilan Siswa Pada Mata Pelajaran Sistem Utilitas Bangunan Kelas XI Di SMKN 5 Surabaya - Ali Hasan Abdullah; Arie Wardhono . (Jurnal Kajian Pendidikan Teknik Bangunan, 2023)
The purpose of this study was to determine the effect of jobsheet media on student skill learning outcomes and to determine the learning outcomes between the treated class and the untreated class in class XI KGSP SMKN 5 Surabaya. This type of research uses quasi-experiment research with a quantitative approach while this research design uses Posttest Only Control Design. While the research subjects were KGSP class XI students in the 2022/2023 academic year consisting of 108 students. The data collection technique uses Posttest test results (performance assessment) which has gone through the reliability and validity test stages. The learning outcomes that have been obtained in the form of data are then analyzed using the Independent Sample t-test. The results obtained showed that the jobsheet was declared feasible to use, indicated by the average value of the learning outcomes of the treated class of 94.71 greater than the average value of the learning outcomes of the untreated class of 78.88. 1) The acquisition of the t-test results obtained the calculation of Thitung of 15.837 compared to Ttabel of 1.997 or it can be interpreted that Thitung> Ttabel. So it can be concluded that the jobsheet has a significant effect on learning outcomes. 2) The learning outcomes obtained through the performance assessment sheet showed that 100% or all students in the treated class were able to exceed the school's KKM. While the learning outcomes obtained through the performance assessment sheet in the untreated class amounted to 73.52%.